ПІДВИЩЕННЯ ЕФЕКТИВНОСТІ КЕРУВАННЯ РЕЖИМАМИ РОЗПОДІЛЬНИХ МЕРЕЖ ЗА УМОВ ЗАСТОСУВАННЯ РОЗОСЕРЕДЖЕНИХ ДЖЕРЕЛ ГЕНЕРАЦІЇ ТА ЗАСОБІВ АКУМУЛЮВАННЯ ЕЛЕКТРОЕНЕРГІЇ - Жаркін, А.Ф.; Новський, В.О.; Попов, В.А.; Ярмолюк, О.С. (Інститут електродинаміки НАН України, Київ, 2021)
New technological solutions have been proposed that allow effective reduction of electrical energy losses in distribution networks with local generation sources and storage units due to the possibility of dynamic control of the network configuration. The conditions for the rational use of remotely controlled switching devices have been substantiated and an algorithm for controlling their operation has been developed. The possibility of using power electronics devices is demonstrated and an approach to their operation is proposed in order to create optimal flows of active and reactive power in the distribution network circuit to minimize energy losses. References 9, figures 3.